Bonjours,aider moi svp ( c'est la derniere note de l'année )



Resoudre chaque équation :


a) -5 + x = -2 + 3 x
4 2 4





b) -x = 2x +7
2 3 6





Developpement



résoudre les équations :


a) (2x - 5) (1+x) =2x(x-3)


b) 6x²-2+(3-2x)(4+3x)=0.

2

Réponses

2014-05-29T14:24:54+02:00
Resoudre chaque équation :
a)
 -5 + x = -2 + 3 x 

3x-x = -5+2
2x = -3
x = -3/2

b)
 -x = 2x +7
2x+x = -7
3x = -7
 x = -7/3

résoudre les équations :
a)
(2x - 5) (1+x) =2x(x-3)
2x+2x²-5-5x = 2x²-6x
-3x-5 = -6x
6x-3x = 5
3x = 5
x = 5/3

b)
 6x²-2+(3-2x)(4+3x)=0.
6x
²-2+12+9x-8x-6x² = 0
10+x = 0
x = -10
2014-05-29T14:28:10+02:00
A) -5 + x = -2 + 3x
x - 3x = -2 + 5
-2x = 3
x = -3/2

b) -x = 2x + 7
-x - 2x = 7
-3x = 7
x = -7/3

a) (2x - 5) (1+x) =2x(x-3)
2x + 2x² - 5 - 5x = 2x² - 6x
2x - 5x + 6x + 2x² - 2x² =  5
3x = 5
x = 5/3

b) 6x²-2+(3-2x)(4+3x)=0
6x² -2 + 3*4 + 3*3x - 4*2x - 2*3x² = 0
6x² - 2 + 12 + 9x - 8x - 6x² = 0
6x² - 6x² -2 +12 + 9x -8x = 0
10 + x = 0
x = -10